2022
DOI: 10.3390/agronomy12020462
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Domestication Concept for Potato Germplasm Enhancement

Abstract: Wild potato germplasm serves as a natural pool of agronomically valuable traits for potato breeding, such as resistance to pathogens and abiotic stresses, quality, and consumer-oriented traits. The introgression of these traits into cultivated potato is hampered by the different kinds of incompatibility and linkages between desirable and undesirable features in hybrid progeny. The trait donor improvement via correction of negative characteristics prior to hybridization to domestic potato can be a solution to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…SGAs are toxic specialized metabolites found in members of the Solanaceae, such as tomato, potato, and eggplant. [205][206][207][208][209] They are classified into solanidane and spirosolane, based on their skeleton derived from the cholesterol side chain. 210,211 Recently, Mizutani's, Aharoni's, and other research groups identified the biosynthetic pathway of SGAs.…”
Section: Steroidal Glycoalkaloids (Sgas)mentioning
confidence: 99%
“…SGAs are toxic specialized metabolites found in members of the Solanaceae, such as tomato, potato, and eggplant. [205][206][207][208][209] They are classified into solanidane and spirosolane, based on their skeleton derived from the cholesterol side chain. 210,211 Recently, Mizutani's, Aharoni's, and other research groups identified the biosynthetic pathway of SGAs.…”
Section: Steroidal Glycoalkaloids (Sgas)mentioning
confidence: 99%
“…These traits are typical for domesticated cereal species. For potatoes, a typical tuberous crop, [ 32 ] suggested targeting self-compatibility ( SRNase ), tuberization under long days and compact plants ( SP5G, CDF1 ), low glycoalkaloid content ( GAME —glycoalkaloid metabolism genes) and short stolons ( GA20ox1 ). We note that whereas there are several review papers that discuss opportunities to re-domesticate or de novo domesticate wild, feral or marginally domesticated crops with new breeding technologies, only a few works report to actually have performed the task.…”
Section: De Novo Domestication: An Emerging Trend In Plant Sciencementioning
confidence: 99%
“…With regard to germplasm collections, it is important to point out that presenting a high genetic variability also means an increase in the possibility of having in the selected genotypes alleles linked to undesirable or even harmful traits, e.g., the susceptibility to a pathogen or the production of a toxic compound. These alleles can segregate with traits of interest (linkage drag), therefore, during the breeding process, careful work of selection against them is necessary [51][52][53].…”
Section: The Role Of Genetics In the Adaptability And Sustainability ...mentioning
confidence: 99%